Search me library and web research (Victoria : Learning Essentials, 2002)
Summary: This video shows the students how to devise a research plan to find the information they need for asignments covering isues such as identifying what information is needed; locating potential sources of information; understanding and best using library resources and successful internet research skills.
Keywords: Study skills; Methods of study